EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL COMMITMENT: A STUDY OF TELECOM INDUSTRY - et al., Dr. Priyanka Ranga (International Journal of Advanced Science and Technology, 2019)
Purpose - The purpose of this paper is to examine the employee engagement and commitment level of telecom sector employees and also to examine the relationship among employee engagement and organizational commitment.Design/Methodology/approach - Three hundred (300) employees of three different organizations of New Delhi and NCR were sampled. Descriptive statistics consisted of mean and standard deviation in order to have a clear picture of study variables. Pearson product correlation, independent t-test and ANOVA were the statistical tools used for analyzing the data collected.Findings-The findings of the study revealed that employees of telecom sector have a low level of employee engagement and commitment and there is a significant positive relationship between employee engagement and employee commitment. With regard to the demographic characteristics of the employees, experience and income significantly influenced employee engagement and commitment. The findings of the study are discussed with reference to the reviewed literature.Practical implications –The present study points out the need for employees to be provided with resources and freedom needed to perform their work roles since it has consequential effects on employee engagement and organizational commitment.Originality/value – This paper attempts to investigate the employee engagement and commitment level of employees and relationship among employee engagement and employee commitment with addition of new insights.